Marketing - Grewal, Dhruv (Pearson, 2016)
Connect Marketing’s assignments provide instant feedback and span the introduction of course concepts to their application and beyond, including iSeeit! concept animations, video cases, case analyses, data analytics exercises, and more. Contact your learning technology representative for a matrix listing assignable assets by learning outcomes.